Effect of chelating agents on shear bond strength of EpoSeal Plus™ sealer to root canal dentin: In vitro study - Prajwal Shetty; Sandya Kini; Nidambur Vasudev Ballal; Nagaraja Upadhaya (Saudi Endodontic Journal, 2021)
Introduction: The aim of the study was to evaluate the effect of 17% ethylenediaminetetraacetic acid (EDTA) and 7% maleic acid (MA) on shear bond strength of EpoSeal Plus sealer to root canal dentin. Materials and Methods: Twenty-one decoronated maxillary central incisors were longitudinally split into two halves, and each half of the root was further split into three sections, coronal, middle, and apical thirds, respectively, and embedded in dental stone block and abraded with silicon carbide paper to create smear layer. Random division of samples was done into Group 1 (n = 12): 0.9% of saline (5 mL/min), Group 2 (n = 15): 17% EDTA (5 mL/min), and Group 3 (n = 15): 7% MA (5 mL/min). After drying the specimens using paper points, polyethylene tubes were placed on the center of the root canal dentin, and EpoSeal Plus sealer was placed into the tubes, followed by which testing of shear bond strength using a universal testing machine was done. One-way ANOVA and Tukey's honestly significant difference post hoc test was done with a significance level (P = 0.05). Results: The results demonstrated significantly more shear bond strength in MA than EDTA in the middle and apical thirds (P < 0.05), whereas no significant difference was observed in the coronal third (P = 0.05). Conclusion: The shear bond strength of EpoSeal Plus was found to be the maximum at all thirds of root canal dentin when irrigated with 7% MA.